Impact of HbA1c reduction on major kidney outcomes in type 2 diabetes with poor glycemic control and advanced CKD (2025)
Aims: In subjects with type 2 diabetes (DM), poor glycemic control, and advanced chronic kidney disease (CKD), the kidney beneft of the reduction of glycated hemoglobin (HbA1c) is not well established. Methods: In a retrospective cohort, we included patients with DM, CKD grade 3b-5, and HbA1c > 9% to evaluate the risk of developing major adverse kidney events (MAKE) defned as the start of kidney replacement therapy (KRT), ≥ 25% or ≥ 40% decline in the glomerular fltration rate (eGFR) from baseline, and death; patients were divided according to the HbA1c levels at the end of the follow-up into the following groups: > 75 mmol/mol (≥ 9.0%), 74–64 mmol/mol (8.9%–8.0%), 64–53 mmol/mol (7.9%–7.0%), and < 52 mmol/mol (< 7.0%). We described their characteristics and analyzed their risks, adjusting for confounding variables. Results: From 2015 to 2023, 111 patients were included. In 46 patients (41.4%), the HbA1c at the end of follow-up (60 months) was still > 75 mmol/mol (≥ 9%), and each patient had a mean of 4.9 HbA1c measurements. Te mean age was 59 years, and 46% were male; the baseline eGFR was 25 mL/min/1.73 m2 . MAKE occurred in 67% of cases. In a multivariate analysis, the risk of MAKE was not associated with the HbA1c groups, nor was it associated with any of the MAKE components individually, nor in certain subgroups. When evaluating the magnitude of percentage changes in HbA1 with the initiation of KRT, we did not fnd any association. Conclusions: With advanced CKD and poor glycemic control, changes in HbA1c during long follow-up are not associated with MAKE or its individual components.